Development and validation of knowledge and attitude on covid-19 infection and vaccination toward pregnancy questionnaire and validation of adult vaccine hesitancy scale (AVHS) among pregnant women. - Mood, Nur Azreen Che (2024)
Pregnancy is one of the risks for severe COVID-19 infection and COVID-19 vaccination hesitancy among pregnant women is still an issue. This study aims to develop and validate the knowledge and attitude (pKAC19) to examine COVID-19 infection and vaccination among pregnant women. It also validates the Pregnancy Vaccine Hesitancy Scale (pVHS) to assess vaccine hesitancy among pregnant women in Malaysia. First phase involved the development of new Knowledge and Attitude (pKAC19) and the adaptation of the aVHS, second phase includes a cross-sectional study for internal validation of the new Knowledge and Attitude (pKAC19) to assess the knowledge and attitude on COVID-19 infection and vaccination toward pregnancy and vaccine hesitancy among pregnant women using EFA. Meanwhile, CFA data collection; a cross-sectional study was conducted to confirm Knowledge and Attitude (pKAC19) validation. During phase 1, face and content validity were performed; meanwhile, during phase 2, EFA and CFA were performed in two locations with larger sample sizes. Six expert panels were involved in content validity after the items for knowledge and attitude and COVID-19 vaccine hesitancy were evaluated. About ten pregnant women were involved in the face validity followed by reliability testing: Exploratory Factor Analysis (EFA) involving 200 pregnant women attending Obstetrics and Gynaecology Clinic, Hospital Universiti Sains Malaysia, Kelantan.